PERAN MAHASISWA KULIAH KERJA NYATA (KKN) DALAM BIDANG BERBASIS MASJID SEBAGAI WUJUD PENGABDIAN DI MASJID NURUL ISLAM DESA PAGAR AGUNG - Anggraini, Tiyas; Mardhiyah , Sakinatul; Putri, Anike; Prasetya , Septian; Agustina , Rindawati; Andriani, Yuniza; Praduita , Andry Rani Putri; Adriana , Delvia; Pratama, Obib Madhandi; Marsilena , Nia (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) in Pagar Agung Village aims to implement students' academic knowledge in community service. This program involves various activities such as community empowerment, educational improvement, and local economic development. Students collaborate with village residents to identify local issues and seek innovative and sustainable solutions. The outcomes of this KKN are expected to enhance the welfare of the Pagar Agung Village community and strengthen the relationship between the university and the local society